2016
DOI: 10.1051/shsconf/20162801132
|View full text |Cite
|
Sign up to set email alerts
|

The problem of professional burnout in stress management

Abstract: Abstract. The problem of professional burnout is extremely relevant in current stress management. By its nature, professional burnout is a unique type of stress syndrome that is characterized by emotional exhaustion. It leads to loss of energy and interest in one's job. A burnout could be the result of such syndromes as -burnout and boreout. It could emerge as the reaction of the organism to the high working intensity and stress working conditions or due to the boredom and absence of the sphere for professiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 10 publications
(7 reference statements)
0
5
0
Order By: Relevance
“…This society is focused not on achieving the best public relations (Fahlquist, & Roeser, 2015), but it strives to provide protection and to avoid the worst. This changes the orientation towards the needs as a well-being foundation, and focuses on self-restriction of these needs (Makasheva et al, 2016). One of the most important conditions for this shift of values is transformation of the social environment and human life-support systems under conditions of life destruction.…”
Section: Social Risk As a Factor Of The Development Of Modern Societymentioning
confidence: 99%
“…This society is focused not on achieving the best public relations (Fahlquist, & Roeser, 2015), but it strives to provide protection and to avoid the worst. This changes the orientation towards the needs as a well-being foundation, and focuses on self-restriction of these needs (Makasheva et al, 2016). One of the most important conditions for this shift of values is transformation of the social environment and human life-support systems under conditions of life destruction.…”
Section: Social Risk As a Factor Of The Development Of Modern Societymentioning
confidence: 99%
“…Previous studies have shown that psychological factors and some key personal resources are strongly associated with job burnout (Bakker & de Vries, 2021 ; Barello et al, 2021 ; Makasheva et al, 2016 ). Some studies have identified variables (e.g., a sense of calling) that may moderate the relationship between psychological distress and job burnout (Jo et al, 2018 ; Slagsvold & Sørensen, 2008 ).…”
Section: Introductionmentioning
confidence: 99%
“…Excessive experience of stress leads to the occurrence of negative consequences in an individual's life. If we talk about experiencing long-term work stress, it can result in burnout syndrome or boreout syndrome (Makasheva et al, 2016). For this reason, our research aimed to examine the relationship between burnout syndrome and boreout syndrome in secondary school teachers during the stress period of the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%